The Use of Fermented Cocoa Pod in Feed on Performance and Income Over Feed Cost (IOFC) of Male Local Sheep - Ardina Kharisma; Hasnudi; Tri Hesty Wahyuni; Armyn Hakim Daulay; Nurzainah Ginting (Jurnal Peternakan Integratif, 2019)
Cocoa pod is one of the cocoa processing wastes which can be used as animal feed.The study aims to find the use of cocoa pod which fermented by bioactivator (MOIYL) in feedon performance and IOFC of male local sheep. The research was conducted at Pak Didit's farmJl. Bunga Rinte, Simpang Selayang, Medan, in October - December 2018 using completelyrandomized design (CRD) with 5 treatments and 4 replications. The experiment used 20 ofmale local sheep weaning with initial body weight of 12.65 ± 1 kg. The treatment such as P0(80% field grass + 20% concentrate), P1 (60% field grass + 20% fermented cocoa pod + 20%concentrate), P2 (40% field grass + 40% fermented cocoa pod + 20% concentrate), P3 (20%field grass + 60% fermented cocoa pod + 20% concentrate), P4 (80% fermented cocoa pod +concentrate 20%). The observed of are feeds consumption, average daily gain, feed conversionratio (FCR), and income over feed cost (IOFC).The results of this research indicated that utilization of fermented cocoa pod in feed improvedthe performance of male local sheep with the average consumption of sheep feed (g/head/day):421.62; 422.60; 524.43; 452.83 and 368.56, average daily gain (g/head/day): 59.95; 60.75;84.19; 67.76 and 40.57, and ration conversion: 7.06; 7.17; 6.43; 6.68 and 9.11 and averageIncome Over Feed Cost (IOFC):141.123,8; 142.837,9; 201.301,0; 159.568,4 and 89.273,7. Theconclusion of this study is that the use of cacao pods fermented with 5% MOIYL in ration ofmale local weaning can be given to the level of 40%.